Five minute recordings of heart rate variability for population studies: repeatability and age–sex characteristics. Issue 2 (1st August 1998) - Sinnreich, R; Kark, J D; Friedlander, Y; Sapoznikov, D; Luria, M H
Abstract : Objective: To evaluate the stability of short recordings of heart rate variability (HRV) with time, and the association of HRV with age and sex. Design: Five minute Holter recordings were made twice over a two month interval (tracking study). In addition, HRV was measured in a cross sectional study. Setting: Residents of 11 Israeli kibbutzim were examined in their settlements. Subjects: 32 men and 38 women (aged 31–67) participated in the tracking study and 294 (aged 35–65) were involved in the cross sectional study. Main outcome measures: Time and frequency domain analyses on Holter recordings were undertaken in two breathing conditions: spontaneous and controlled breathing (15 respirations per minute). Regression was used to assess the relations of sex, age, heart rate, and logarithmically transformed HRV indices. Results: HRV measures were highly consistent with time with correlations of 0.76–0.80 for high frequency and total power. Geometric mean total power declined with age by 45% in men and 32% in women, and was lower by 24% among women than among men (all p ⩽ 0.005). Men had a 34% higher very low and low frequency power and a higher ratio of low to high frequency power (p < 0.001). Conversely, high frequency power in women represents a greater proportion of total power than in men. Conclusion: Short recordings of HRV in a non-laboratory setting are stable over months and therefore characteristic of an individual. Strong age and sex effects were evident. HRV derived from short recordings can be informative in population based studies.